Kinematic study with and without ski boots using ski simulator - Lee, H. T.; Kim, Y. J.; Kim, Y. S. (Science & Sports, 2017)
Objectives: We performed a comparative analysis of ski simulators, which remove seasonal and regional constraints, to effectively improve training methods. Equipment and methods: We compared the kinematic characteristics with and without ski boots on the ski simulator and found significant differences in lower limb joint angles, run-time, muscle activity, and heart rate. Results: Based on these results, we suggest the following exercise guidelines for ski simulators: (i) simulator skiing without boots results in a wider range of motion (ROM) and can be utilized as low-intensity exercise to improve muscle endurance and balance and (ii) simulator skiing with boots enables faster movements within a limited range and can help improve muscle strength. These results are not limited to ski training; they can also be applied to specialized exercise improvement and strengthening programs as well as physical training.